Transformation of SNAC1 under Stress Inducible Promoter Rd29a Confers High Yield and Stress Tolerance in Rice (Plant Tissue Culture and Biotechnology, 2023)
Abiotic stress tolerance in plants is often induced by activation of transcription factors. An increased stress tolerance was observed in indica rice cultivar BRRI dhan55 after transforming with the transcription factor SNAC1 (stress responsive NAC1) under stress inducible promoter rd29A that minimized unexpected phenotype and metabolic burden in transgenic lines. Tissue culture independent Agrobacterium-mediated in planta transformation method was used. Molecular analyses confirmed the successful integration of the SNAC1 gene and significantly higher gene expression level in the transgenic lines. The transgenic lines showed 3:1 segregation ratio at T2 generation following the Mendelian law of inheritance. Assays for leaf disk senescence and chlorophyll content at 100 mM and 200 mM salt and survival rates at 200 mM salt and drought conditions at 12 days of water withdrawal and after recovery under water showed significantly increased stress tolerance in the transgenics lines at seedling stage compared to the wild type. Enhanced yield, spikelet fertility, and 100 grain weight were observed at the reproductive stage compared to wild type under both salinity and drought stress conditions. Thus, SNAC1 expression in plants under inducible promoter is a better choice to enhance stress tolerance and yield under salinity and drought conditions.Plant Tissue Cult. & Biotech. 33(2): 115-133, 2023 (December)